2018
DOI: 10.1016/j.envpol.2018.09.096
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the fate of antibiotic resistance genes during thermochemical pretreatment and anaerobic digestion of pharmaceutical waste sludge

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 57 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the link between microbial phylogeny and the resistome was supported by Procrustes analyses, as the resistome correlated significantly with microbial communities during composting (sum of squares M 2 = 0.3578–0.6486, P < 0.001, based on 9999 permutations, Figure S10), along with correlation analyses, as the absolute abundances of ARGs correlated significantly with those of 16S rRNA genes during composting (Pearson r = 0.9390, P < 0.001, Figure S2). These findings further supported the notions that the resistome profile during composting is largely dependent on the microbial genotype and that a greater microbial diversity enhances the dissemination of ARGs . In order to more specifically investigate the association between ARGs and microbial communities during composting, we constructed co-occurrence networks that were, for the first time, based on ARG datasets and a wide range of microbial communities (bacterial, fungal, and protistan).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the link between microbial phylogeny and the resistome was supported by Procrustes analyses, as the resistome correlated significantly with microbial communities during composting (sum of squares M 2 = 0.3578–0.6486, P < 0.001, based on 9999 permutations, Figure S10), along with correlation analyses, as the absolute abundances of ARGs correlated significantly with those of 16S rRNA genes during composting (Pearson r = 0.9390, P < 0.001, Figure S2). These findings further supported the notions that the resistome profile during composting is largely dependent on the microbial genotype and that a greater microbial diversity enhances the dissemination of ARGs . In order to more specifically investigate the association between ARGs and microbial communities during composting, we constructed co-occurrence networks that were, for the first time, based on ARG datasets and a wide range of microbial communities (bacterial, fungal, and protistan).…”
Section: Resultssupporting
confidence: 59%
“…These findings further supported the notions that the resistome profile during composting is largely dependent on the microbial genotype 16 and that a greater microbial diversity enhances the dissemination of ARGs. 88 In order to more specifically investigate the association between ARGs and microbial communities during composting, we constructed co-occurrence networks that were, for the first time, based on ARG datasets and a wide range of microbial communities (bacterial, fungal, and protistan). Due to differences in the variation of persistent and transient ARGs, ARG−microbe networks were evaluated separately for these two datasets (Figure 5a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Literature reports demonstrated that most ARGs and MGEs were reduced after the pretreatment. However, their abundances increased again after the AD process which is called the rebound effect (Ma et al 2011 ; Pei et al 2016 ; Tong et al 2018 , 2019 ; Wang et al 2019a ; Sun et al 2019a ). Since the treatment significantly removes ARGs in the feedstock, the increase of resistance genes during AD could be attributed to the seed inoculum used in the systems (Ma et al 2011 ; Pei et al 2016 ).…”
Section: Factors Affecting the Fate Of Args In Ad Processesmentioning
confidence: 99%
“…Moreover, mitigating the spread of ARGs in the environment is essential to reduce potential health risks. There are several pathways through which ARGs can be released to the environment such as manure land application (Tien et al, 2017), disposal of poorly treated pharmaceutical sludge (Tong et al, 2018), and digestate land application (Derongs et al, 2020).…”
Section: Introductionmentioning
confidence: 99%